Structural and functional improvement of injured brain after severe acute carbon monoxide poisoning by stem cell-based therapy in rats - Jiang, Guoping; Gao, Jianping; Xu, Yongshan; Ma, Yuefeng; Jiang, Guanyu; Yan, Weiqi (Critical care medicine, 2009)
We investigated the feasibility and efficacy of bone marrow mesenchymal stem cells (BMSCs)-derived neural stem-like cells (MS-NSCs) therapy on injured brain in rats after severe acute carbon monoxide (CO) poisoning. Controlled animal study. Research laboratory of a university hospital. Sprague-Dawley rats weighing 230 +/- 20 g and 90 +/- 10 g. The rats were exposed to 1000 ppm CO in air for 40 minutes and then to 3000 ppm for another 20 minutes until they lost consciousness. Approximately 7 x 10 allogeneic BMSCs or MS-NSCs labeled with BrdU were infused into the poisoned rats via the internal carotid after a 24-hour resuscitation. The rats with and without CO poisoning were used as placebo and sham controls, respectively. The neurologic and cognitive functions were evaluated by Neurologic Severity Scores and Morris water maze tests. Examinations with immunohistochemistry, myelin, and hematoxylin-eosin staining were made to assess cerebral structure after 5 weeks. Histologically, the compactness and arrangement of the insulted white matter were improved by the cellular treatments. The transplanted MS-NSCs were positive for microtubule-associated protein 2 in hippocampus, 84.6% +/- 5.6%, and for glial fibrillary acidic protein in subventricular white matter and hippocampus, 32.2% +/- 2.5% and 9.7% +/- 1.2%, respectively, although the MS-NSCs group showed a larger fraction in the expression of the above markers in corresponding domains compared with the BMSCs group. The MS-NSCs also displayed a higher survival rate than BMSCs in most domains of diffusively injured brain, leading to a better improvement in the Morris water maze test (p < 0.05). The stem cell-based therapy could be advantageous for improving the structure and function of injured brain in rats after severe acute CO poisoning, indicating the potential use as a novel approach for severely CO-poisoned patients with delayed neurologic sequelae. Furthermore, MS-NSCs may render better therapeutic effects after neurologic injury than untreated BMSCs.